KONTRIBUSI KETERAMPILAN MENYIMAK PANTUN TERHADAP KETERAMILAN MENULIS PANTUN SISWA KELAS VII SMP NEGERI 2 LUBUK ALUNG - Setia, Welli; Gani, Erizal; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2016)
ABSTRACTÂ This article is written to discuss the results of research on the contribution of listening skills rhyme to rhyme writing skills of students of class VII SMPN 2 Lubuk Alung. This research data in the form of score results rhymes listening skills and writing skills scores results rhymes. The data was obtained through two types of test, which is an objective test to measure listening skills rhymes and performance tests to measure the skills of writing rhymes. This research is a quantitative correlation method. The results of this research are three: (1) listening skills rhyme VII SMPN 2 Lubuk Alung currently on qualifications Good (B) with an average value of 77.28, (2) the skill of writing rhymes seventh grade students of SMPN 2 Lubuk Alung located the qualification Good (B) with an average value of 77.27, and (3) listening skills contribute to the writing skills rhyme rhyme by 89.5% and the remaining 10.5% is influenced by other factors in this study.Â Kata kunci: kontribusi, menyimak, menulis, pantun